Development of fixed abrasive chemical mechanical polishing process for glass disk substrates - Tian, Ye Bing (2016)
Glass disk substrates are used in a wide range of portable devices because of their relatively high resistance to heat and shocks compared to aluminum substrates. Chemical mechanical polishing (CMP) with fixed abrasive pad is an alternative glass disk substrates finishing method to loose abrasive lapping and polishing with traditional pad. In this paper, we developed a chemical mechanical polishing process for 2.5-inch glass disk substrates using a fixed abrasive pad. A serial of CMP experiments were carried out under different polishing variables and conditioning modes (ex situ and in situ conditioning). The polishing performances were evaluated and analyzed in terms of surface roughness, surface topography, and material removal rate. The polishing characteristics were also discussed to reveal material removal mechanism and surface generation involved in fixed abrasive CMP for glass disk substrates.